2015
DOI: 10.4314/sajas.v45i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prebiotics and probiotics on the performance and bacterial colonization of broiler chickens

Abstract: A study was undertaken to evaluate the effects of Neoxyval (antimicrobial growth promoter (AGP)), TechnoMos (prebiotic), GalliPro (probiotic) and a mixture of TechnoMos and GalliPro (symbiotic) on growth performance, carcass yield, histomorphology and intestinal bacterial counts in broilers (0 d to 42 d). Two hundred day-old Ross (308) broilers were allocated to five experimental treatments: T1 = control (CONT), T2 = T1 + Neoxyval, T3 = T1 + Gallipro, T4 = T1+ TechnoMos and T5 = T1+ Gallipro+ TechnoMos. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 34 publications
3
29
2
5
Order By: Relevance
“…Quantification of selected species of bacteria belonging to pathogenic or non-pathogenic group showed that non-pathogenic bacteria (Bifidobacteria and Enterococci) greatly increased along with decrease in pathogenic ones (E. coli, Clostridia, Enterobacteria and Campylobacter). This is a strong prebiotic-like effect as such reported with usage of known prebiotics (Guo et al 2004;Abudabos et al 2015). To the best of our knowledge, this is the first study reporting such effect for dietary TRP.…”
Section: Discussionsupporting
confidence: 59%
“…Quantification of selected species of bacteria belonging to pathogenic or non-pathogenic group showed that non-pathogenic bacteria (Bifidobacteria and Enterococci) greatly increased along with decrease in pathogenic ones (E. coli, Clostridia, Enterobacteria and Campylobacter). This is a strong prebiotic-like effect as such reported with usage of known prebiotics (Guo et al 2004;Abudabos et al 2015). To the best of our knowledge, this is the first study reporting such effect for dietary TRP.…”
Section: Discussionsupporting
confidence: 59%
“…It could be due to the ine cacy of PrimaLac® probiotic to colonise in the intestines. This result was in contrast with the previous studies, where probiotic supplementation was found to increase the level of probiotic bacteria in chicken intestines [36,49,54]. It also need to be highlighted that in the current study, PrimaLac® probiotic microbes such as Enterococcus faecium and Aspergillus oryzae were not quanti ed, where their populations might be elevated in probiotic supplemented groups.…”
Section: Discussioncontrasting
confidence: 97%
“…In the current study, chickens from probiotic supplemented groups (P, 1 P and 2 P) had signi cantly lower population of C. perfringens compared to the control at 21 d caeca. This result was consistent with previous studies, in which C. perfringens population was signi cantly lower in chickens supplemented with probiotic [49]. This was due to the protective roles of probiotic in reducing pathogens based on the reported mode of actions of competitive exclusion [48,42] and antagonistic activity [44,43,32,60].…”
Section: Discussionsupporting
confidence: 92%
“…Probiotics have garnered interest as the alternative to AGP [6][7][8][9]. Probiotics can inhibit the growth of enteric pathogens and the development of subsequent diseases by producing antimicrobial substances in livestock [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%